Does Argentine ant invasion affect prey availability for foliage-gleaning birds? - Estany-Tigerström, David; Bas, Josep Maria; Pons, Pere (Biological Invasions, 2009)
Food availability during the breeding season plays a critical role in reproductive success of insectivorous birds. Given that the invasive Argentine ant (Linepithema humile) is known to alter arthropod communities, we predicted that its invasion may affect the availability of food resources for coexisting foliage-gleaning birds. With this aim we studied, for 3 years, foliage arthropods occurring on cork oaks (Quercus suber) and tree heaths (Erica arborea) in invaded and non-invaded secondary forests of the northeastern Iberian Peninsula. Our results show that Argentine ants interact with arboreal foliage arthropods in a different manner than the native ants they displace do. The invasive ant impacted the arthropod community by reducing order diversity and ant species richness and by causing extirpation of most native ant species. Arthropod availability for foliage gleaners’ nestlings diminished in invaded cork oaks, mainly responding to the abundance and biomass depletion of caterpillars. Results suggest that the reproduction of canopyforaging foliage-gleaning species that mostly rely on caterpillars to feed their young could be compromised by the Argentine ant invasion. Thus, the Argentine ant could be promoting bottom-up effects in the trophic web through its effects on the availability of arthropod preys for insectivorous birds.
Keywords: arborea á; Biological invasion; biological invasion á erica; birds á; Erica arborea; Foliage arthropods; foliage arthropods á insectivorous; Insectivorous birds; Linepithema humile; linepithema humile á quercus; Quercus suber; suber

Does Argentine ant invasion affect prey availability for foliage-gleaning birds? - Estany-Tigerström, David; Bas, Josep Maria; Pons, Pere (Biological Invasions, 2009)
Food availability during the breeding season plays a critical role in reproductive success of insectivorous birds. Given that the invasive Argentine ant (Linepithema humile) is known to alter arthropod communities, we predicted that its invasion may affect the availability of food resources for coexisting foliage-gleaning birds. With this aim we studied, for 3 years, foliage arthropods occurring on cork oaks (Quercus suber) and tree heaths (Erica arborea) in invaded and non-invaded secondary forests of the northeastern Iberian Peninsula. Our results show that Argentine ants interact with arboreal foliage arthropods in a different manner than the native ants they displace do. The invasive ant impacted the arthropod community by reducing order diversity and ant species richness and by causing extirpation of most native ant species. Arthropod availability for foliage gleaners’ nestlings diminished in invaded cork oaks, mainly responding to the abundance and biomass depletion of caterpillars. Results suggest that the reproduction of canopyforaging foliage-gleaning species that mostly rely on caterpillars to feed their young could be compromised by the Argentine ant invasion. Thus, the Argentine ant could be promoting bottom-up effects in the trophic web through its effects on the availability of arthropod preys for insectivorous birds.
Keywords: arborea á; Biological invasion; biological invasion á erica; birds á; Erica arborea; Foliage arthropods; foliage arthropods á insectivorous; Insectivorous birds; Linepithema humile; linepithema humile á quercus; Quercus suber; suber

Canopy recovery after drought dieback in holm-oak Mediterranean forests of Catalonia (NE Spain) - Lloret, Francisco; Siscart, Daniel; Dalmases, Carles (Global Change Biology, 2004)
Climate change is likely to produce more frequent and longer droughts in the Mediterranean region, like that of 1994, which produced important changes in the Quercus ilex forests, with up to 76% of the trees showing complete canopy dieback. At the landscape level, a mosaic of responses to the drought was observed, linked to the distribution of lithological substrates. Damage to the dominant tree species (Q. ilex) and the most common understorey shrub (Erica arborea) was more noticeable on the compact substrates (breccia) than on the fissured ones (schist). This result was consistent with observations documenting deeper root penetration in schist than in breccia materials, allowing the plants growing on fissured substrates to use water from deeper soil levels. Smaller plants were more vulnerable to drought than larger plants in the trees, but not in the shrubs. Overall, Q. ilex was more affected than E. arborea. The resilience of the system was evaluated from the canopy recovery 1 year after the episode. Stump and crown resprouting was fairly extensive, but the damage pattern in relation to substrate, plant size, and species remained similar. The effect of recurrent drought episodes was studied on vegetation patches of Q. ilex located on mountain slopes and surrounded by bare rock. We observed that plants that resprouted weakly after a previous drought in 1985 were more likely to die or to produce poor regeneration in 1995 than plants that had resprouted vigorously. Vegetation patches located on the lower part of the slope were also less damaged than patches situated uphill. The study provides evidence of relevant changes in forest canopy as a consequence of extreme climate events. The distribution of this effect across the landscape is mediated by lithological substrate, causing patchy patterns. The results also support the hypothesis that recurrent droughts can produce a progressive loss of resilience, by depleting the ability of surviving plants to regenerate.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: climate change; Erica arborea; Quercus ilex; resilience; resprouting; severity; shift; threshold

Soil persistence and biodiversity of ericoid mycorrhizal fungi in the absence of the host plant in a Mediterranean ecosystem. - Bergero, Roberta; Girlanda, Mariangela; Bello, Federica; Luppi, Anna Maria; Perotto, Silvia (Mycorrhiza, 2003)
The occurrence of suitable mycorrhizal inocula may be an important factor affecting the dynamics of plant communities. We investigated the persistence and diversity of ericoid mycorrhizal fungi in the soil of a mature Quercus ilex forest where ericaceous hosts were absent. Erica arborea was used as a bait plant and results were compared to soil samples from experimental plots where cuttings had allowed reappearance of this ericaceous species. Fungal endophytes were isolated and tested in mycorrhiza resynthesis trials. Sterile mycorrhizal endophytes were assigned to morphotypes whose consistency was confirmed by ITS-RFLP. The ITS region of a representative of each morphotype was sequenced. BLAST searches and Neighbour-Joining analysis indicated taxonomic affinities with different classes within Ascomycota. Our results indicate that ericoid mycorrhizal fungi persist and maintain mycorrhizal ability in habitats lacking the ericaceous host. Their persistence could favour the establishment of E. arborea seedlings in pure Q. ilex forests after disturbance phenomena.
Keywords: Erica arborea; Mediterranean ecosystem; Plant succession; Post-cutting; Quercus ilex

Soil persistence and biodiversity of ericoid mycorrhizal fungi in the absence of the host plant in a Mediterranean ecosystem. - Bergero, Roberta; Girlanda, Mariangela; Bello, Federica; Luppi, Anna Maria; Perotto, Silvia (Mycorrhiza, 2003)
The occurrence of suitable mycorrhizal inocula may be an important factor affecting the dynamics of plant communities. We investigated the persistence and diversity of ericoid mycorrhizal fungi in the soil of a mature Quercus ilex forest where ericaceous hosts were absent. Erica arborea was used as a bait plant and results were compared to soil samples from experimental plots where cuttings had allowed reappearance of this ericaceous species. Fungal endophytes were isolated and tested in mycorrhiza resynthesis trials. Sterile mycorrhizal endophytes were assigned to morphotypes whose consistency was confirmed by ITS-RFLP. The ITS region of a representative of each morphotype was sequenced. BLAST searches and Neighbour-Joining analysis indicated taxonomic affinities with different classes within Ascomycota. Our results indicate that ericoid mycorrhizal fungi persist and maintain mycorrhizal ability in habitats lacking the ericaceous host. Their persistence could favour the establishment of E. arborea seedlings in pure Q. ilex forests after disturbance phenomena.
The following values have no corresponding Zotero field: accession-num: 12682828
Keywords: Erica arborea; Mediterranean ecosystem; Plant succession; Post-cutting; Quercus ilex

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R; Perotto, S; Girlanda, M; Vidano, G; Luppi, a M (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R.; Perotto, S.; Girlanda, M.; Vidano, G.; Luppi, a M. (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11050558
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology

Grazing alone is not enough to maintain landscape diversity in the Montseny Biosphere Reserve - Bartolomé, J; Franch, J (Agriculture, Ecosystems & Environment, 2000)
Conservative land-use over the past few decades has converted the Montseny Biosphere Reserve (Spain) from the original open, patchy landscape to almost continuous woodland. Small ruminant grazing is virtually the only major remaining utilisation activity yet little is known about its role in the changing vegetation of the Reserve. This study was undertaken to determine the effects of current grazing practice on its main vegetation components. Three ﬂocks, composed of sheep and goats, that graze yearlong on three separate ranges in the Reserve were selected for study. The ranges represent the wooded slopes and the shrubby upland (altiplano) in the area. Biomass consumption by the ﬂocks was estimated by calculation of normative requirements for observed production and the botanical composition of the livestock diets over a whole annual cycle was determined by micro-histological analysis of the faeces. Production of herbaceous vegetation was determined by clipping sample quadrats, the production of the woody vegetation was derived from previous work in the Reserve. It was found that grazing removed a very small proportion of the dominant Holm oak (Quercus ilex) on the slopes, and a moderate fraction of the shrubby and herbaceous vegetation on the altiplano. Only the heath tree (Erica arborea), an edible shrub in the woodlands, was relatively heavily grazed. It is concluded that grazing alone is not enough to maintain the open, diverse landscape with its many natural values. As in other northern Mediterranean countries, under-utilisation of these woodlands is becoming a serious problem that is also increasing the ﬁre hazard. Maintaining landscape diversity in the region is a complex challenge that land managers should recognise
Keywords: calluna vulgaris; Erica arborea; mediterranean rangeland; Quercus ilex; small ruminants

Grazing alone is not enough to maintain landscape diversity in the Montseny Biosphere Reserve - Bartolomé, J.; Franch, J. (Agriculture, Ecosystems & Environment, 2000)
Conservative land-use over the past few decades has converted the Montseny Biosphere Reserve (Spain) from the original open, patchy landscape to almost continuous woodland. Small ruminant grazing is virtually the only major remaining utilisation activity yet little is known about its role in the changing vegetation of the Reserve. This study was undertaken to determine the effects of current grazing practice on its main vegetation components. Three ﬂocks, composed of sheep and goats, that graze yearlong on three separate ranges in the Reserve were selected for study. The ranges represent the wooded slopes and the shrubby upland (altiplano) in the area. Biomass consumption by the ﬂocks was estimated by calculation of normative requirements for observed production and the botanical composition of the livestock diets over a whole annual cycle was determined by micro-histological analysis of the faeces. Production of herbaceous vegetation was determined by clipping sample quadrats, the production of the woody vegetation was derived from previous work in the Reserve. It was found that grazing removed a very small proportion of the dominant Holm oak (Quercus ilex) on the slopes, and a moderate fraction of the shrubby and herbaceous vegetation on the altiplano. Only the heath tree (Erica arborea), an edible shrub in the woodlands, was relatively heavily grazed. It is concluded that grazing alone is not enough to maintain the open, diverse landscape with its many natural values. As in other northern Mediterranean countries, under-utilisation of these woodlands is becoming a serious problem that is also increasing the ﬁre hazard. Maintaining landscape diversity in the region is a complex challenge that land managers should recognise
Keywords: calluna vulgaris; Erica arborea; mediterranean rangeland; Quercus ilex; small ruminants

Diet selection by sheep and goats on Mediterranean heath-woodland range - Bartolomé, J.; Franch, J.; Plaixats, J.; Seligman, N. G. (JOURNAL OF RANGE MANAGEMENT, 1998)
The study determined the species components of the diets of small ruminants grazing mountain ranges of the Montseny Biosphere Reserve (Catalunya, NE Spain). Three mixed flocks of sheep and goats, led by shepherds, were monitored for a year. Animals grazed a mountain rangeland composed of Qeurcus ilex woodland and Calluna-Erica heathland during the day and were returned to their corrals every night. Diet selection was estimated using fecal analysis. Of the 111 species that were identified, 71 were common to both sheep and goat. Of these, 23 were represented in proportions of more than 1% of the annual diet. Even though goats and sheep grazed together, their diets were significantly different (p < 0.0001), the animal factor accounting for 18% to 60% of the total variation among the main diet components. Variation between seasons was also a major (5% to 56%) highly significant factor, while differences between flocks accounted for a significant, but relatively small part (3% to 10%) of the total variation in diet. The outstanding difference was the avoidance of the tree, Quercus ilex, by the sheep while the goats selected it throughout the year. Sheep selected graminoids throughout the year while goats tended to avoid them. For the rest there.was substantial overlap in species composition between the diet of sheep and goats, especially when analysed over an entire cycle.
The following values have no corresponding Zotero field: pub-location: 445 UNION BLVD, STE 230, LAKEWOOD, CO 80228-1259 USA publisher: SOC RANGE MANAGEMENT
Keywords: calluna vulgaris; Erica arborea; fecal analysis; microhistological analysis; Quercus ilex

Diet selection by sheep and goats on Mediterranean heath-woodland range - Bartolomé, J; Franch, J; Plaixats, J; Seligman, N G (JOURNAL OF RANGE MANAGEMENT, 1998)
The study determined the species components of the diets of small ruminants grazing mountain ranges of the Montseny Biosphere Reserve (Catalunya, NE Spain). Three mixed flocks of sheep and goats, led by shepherds, were monitored for a year. Animals grazed a mountain rangeland composed of Qeurcus ilex woodland and Calluna-Erica heathland during the day and were returned to their corrals every night. Diet selection was estimated using fecal analysis. Of the 111 species that were identified, 71 were common to both sheep and goat. Of these, 23 were represented in proportions of more than 1% of the annual diet. Even though goats and sheep grazed together, their diets were significantly different (p < 0.0001), the animal factor accounting for 18% to 60% of the total variation among the main diet components. Variation between seasons was also a major (5% to 56%) highly significant factor, while differences between flocks accounted for a significant, but relatively small part (3% to 10%) of the total variation in diet. The outstanding difference was the avoidance of the tree, Quercus ilex, by the sheep while the goats selected it throughout the year. Sheep selected graminoids throughout the year while goats tended to avoid them. For the rest there.was substantial overlap in species composition between the diet of sheep and goats, especially when analysed over an entire cycle.
Keywords: calluna vulgaris; Erica arborea; fecal analysis; microhistological analysis; Quercus ilex

Screening of 18 Mediterranean plant species for volatile organic compound emissions - Owen, S; Boissard, C; Street, R A; Duckham, S C; Csiky, O; Hewitt, C N (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.
Keywords: Arbutus unedo; Biogenic emissions; branch enclosure; Chrysanthemum praecox; cistus incanus; Cistus salvifolius; Cytisus sp.; Dittrichia sp.; Erica arborea; Erica multiflora; Helichrysum stoechas; isoprene; Juniperus oxycedrus; Juniperus phoenicea; Monoterpene; myrtus communis; Phillyrea angustifolia; Pinus pinea; Quercus cerris; Quercus ilex; Rubus fruticosus; Spartium junceum; VOCs